A brincadeira no espaço hospitalar : um estudo etnográfico do efeito terapêutico à criança enferma - Oliveira, Marlene Gonçalves de (2015)
This study gather the line of research of Culture, Body Language and Education, Graduate of the Federal University of Mato Grosso program, and aims to realize the outcome of play and Therapeutic Toy (BT) on hospitalized students in Hospital school of Cuiabá-MT. The game is an important activity for children, because it is the basis of their corporeality, when acts a decisive role in motor development, emotional, mental and social. The action of the play is studied by wide possibility that the toy object provides to the child; it is the way that he communicates with the ambient that he lives and express your feelings, besides composing with the socio-cultural aspect. The playfulness, considered as a state of mind, is the feeling originated in the play. Researchers from the Socio-anthropology have in the toy the idea that this object is imbued with content of adult‘s imaginary, which demonstrates the effect that the component imputes on the play, and originate the principle that each child puts his imagination in play, negating the idea of the play is leading by toy object. In 2005 the Federal Law No. 11,105 constituted the hospital playroom. Nursing, through its Federal Council enacted Resolution No. 295/2004, which stipulates the Therapeutic Play (BT) for hospitalized children. This instrument is a compound of objects of health (needles, syringes, dressing materials) and objects of play (dolls and dolls) and its contribution is attach with the child's preparation for painful therapeutic procedures, this makes care becomes efficient and specific. We consider the hospitalized students and their participation in the toy room as a form of play in children's daily lives and the BT a tool of care. It is a qualitative study of ethnographic type, in the interpretativecomprehensive domain; it has been used participant observation to capture the data, that processed in a continuous context, interactively, drift descriptive account of the experienced. The results indicate that the play in the hospital is typical pleasurable routine deriving of the theory of play; the child establishes his particularity in the game, even being conducted activity systematically by adults; The playfulness was the effect shown in the games the hospital ambient. The BT confirms forms of the theory of play; in the first with the game of the educational process - "I teach you to take care of the doll and then you do the same"; in the second is a means to communicate the procedure to be experienced; in the third, the most important feature for the child, play leading to playfulness, a fact inherent in the childhood‘s nature, and found out with the child's imagination.